Endothelial cell proliferation and extracellular matrix-related pathways regulate pulmonary arterial hypertension in rat models - LU Xiaoxuan, GUO Lina, ZHANG Hong, SONG Wanlu, HU Yufei, YANG Peiran (Jichu yixue yu linchuang, 2025)
Objective To identify mechanisms regulating disease progression in rat models of pulmonary arterial hypertension (PAH). Methods Rat PAH models were established using subcutaneous monocrotaline (MCT) injection and the SU5416/hypoxia (SU/Hx) method. Transcriptomic sequencing of lung tissues was performed to identify gene expression and pathway alterations in PAH rats, followed by a comparative analysis with transcriptomic data of patients with idiopathic pulmonary arterial hypertension (IPAH) in NCBI database. Results Inflammatory-related genes such as CXCL9, CCL24, and SECTM1 were upregulated in both PAH rat models and IPAH patient lungs, while genes such as DGKG and DOCK9 were downregulated(P＜0.05). Pathways related to endothelial cell proliferation regulation and extracellular matrix (ECM) remodeling were significantly upregulated(P＜0.05). Conclusions The imbalance in endothelial cell proliferation and abnormal ECM remodeling may collectively contribute to PAH pathogenesis. Further exploration of these signaling pathways may provide deep insights for early diagnosis and targeted therapy of PAH.